Reimagining Audiovisual Media Platform Regulations Through Policy Principles: A Case Study of Taiwan's Endeavor in Crafting Legislation for OTT TV - Chih-Liang Yeh (International Telecommunications Society (ITS), 2024)
In September 2020, the NCC initiated an investigation into the video service "Hualien Haokan" provided through a dedicated set-top box and held a public briefing to draft regulations classifying this service as a cable television service. Such new types of services often face unclear positioning issues globally. Some regulations are based on policies and frameworks established by traditional media, while others are "temporary" strategies specifically designed to address new media issues. These regulations, formed through compromises or expedient measures, cause significant challenges for the development of the audiovisual media services industry and result in substantial regulatory discrepancies between different industries. Picard & Picard (2017) proposed "Policy Principles for the Digital Age," intending to offer guidance to regulatory authorities or policymakers in various countries. These principles, based on normative foundations and values, aim to provide responses that are adaptive to the rapid changes in technology, policy, economy, and society while maintaining continuity. The paper intends to analyze the appropriateness of Taiwan's audiovisual media service regulations and the relationship between specific administrative measures and regulations using Picard & Picard's Policy Principles. Furthermore, it seeks to propose suitable legislative models for imposing obligations, offering feasible legal suggestions for future amendments to audiovisual media service regulations.
Keywords: 330; Audiovisual Media Services; OTT TV; Policy Principles; Legislation